Performance in attentional tasks following meditative focusing and focusing without meditation - Raghavendra, B. R. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND/AIMS: Ancient Indian yoga texts have described four mental states. These are caïcalatä (random thinking), ekāgratā (focusing without meditation), dhāraṇā (meditative focusing), and dhyāna (defocused meditative expansiveness). A previous study compared the performance in a cancellation task at the beginning and end of each of the four mental states (practiced for 20 minutes each, on four separate days) showed an increase in the scores after dhāraṇā Hence, the present study was designed to assess the effects of dhāraṇā (meditative focusing) and ekāgratā (focusing without meditation) on two attention tasks (i) d2 test of attention and (ii) digit symbol substitution test. MATERIALS AND METHODS: Sixty normal healthy male volunteers with ages ranging from 17 to 38 years (group mean age ± S.D., 24.87 ± 4.95) were studied. Assessments were made before and after the practice of ekāgratā and dhāraṇā on two separate days. RESULTS: After both types of focusing, there was a significant improvement in all measures of the d2 test of attention (TN, E, TN-E, E%, and CP). However, the performance in the digit symbol substitution test was better after dhāraṇā but did not change after ekāgratā. CONCLUSIONS: Hence, in summary, dhāraṇā (meditative focusing) and ekāgratā (focusing without meditation) produce nearly comparable results though dhāraṇā (meditative focusing) results in better incidental learning and better accuracy (as assessed by the substitution task).